‘When somebody tells you who you are’ - Milena Parland (Approaching Religion, 2023)
This article investigates the notion of spiritual appropriation in Finnish schools, with a particular focus on the experiences of religious minorities. It draws on narratives from these communities, shedding light on their daily experiences in the educational setting. Employing counter-storytelling from critical race theory (CRT), the research examines the power dynamics and the impact of epistemological privileges within Finnish schools.